Amílcar Cabral, o pedagogo da revolução - da Silva, Marcelo (2022)
Paulo Freire called the independence leader of Guinea-Bissau and Cape Verde, Amílcar Cabral, the “Pedagogue of the Revolution”. Despite being little studied in Brazil, Amílcar Cabral is recognized worldwide as one of the African icons of resistance to European colonialism. In this article, we highlight how Amílcar Cabral inspired Paulo Freire in studies on the African continent, during the period he participated in literacy projects on the continent for the education of subalternized peoples. In this sense, we intend to bring contributions, both by explaining that the colonial heritage is still present due to the effects of coloniality, as well as some possible confrontations in the anti-colonial struggle, looking at the past, to understand the present time.